IGF-1 and PTEN regulate the proliferation and invasiveness of colon cancer cells through opposite effects on PI3K/Akt signalling - Ma, Jiachi; Sawai, Hirozumi; Matsuo, Yoichi; Yasuda, Akira; Ochi, Nobuo; Takahashi, Hiroki; Wakasugi, Takehiro; Funahashi, Hitoshi; Sato, Mikinori; Takeyama, Hiromitsu (Archives of Medical Science, 2009)
Introduction: The tumour suppressor protein phosphatase and tensin homologue deleted on chromosome 10 (PTEN) is a critical tumour suppressor which acts by suppressing tumour cell invasiveness and proliferation and promoting apoptosis through its antagonism of PI3K. Despite its importance, the underlying mechanism of the molecule which regulates phosphorylated PTEN expression is still undefined. Material and methods: We herein investigate the mechanism by which IGF-1 affects cell proliferation (WST-1 cell proliferation assay) and invasion by examining its potential suppression of PTEN activity (with RNA interference) and its interaction with the PI3K/PTEN/Akt/AP-1 signalling pathway in colon cancer cells (HT-29, WiDr, CaCo-2 and Colo320). In addition, we also examine how the knockdown of PTEN influences proliferation and invasion and correlates with IGF-1/IGF-1R/PI3K/Akt/AP-1, and determine PTEN up/downstream targets that preferentially contribute to tumourigenesis. Results: Blockage of PTEN phosphorylation led to a stronger enhancement of cell proliferation and invasion upon stimulation with IGF-1 via its activation of the PI3K/Akt/AP-1 signalling pathway. Furthermore, knockdown of PTEN by siRNA transfection was also found to enhance the activation of the PI3K/Akt/AP-1 pathway, thereby promoting cell invasion and proliferation. IGF-1 induced transcriptional down-regulation of activated PTEN and this signalling pathway promotes cell survival. Conclusions: The IGF-1/PI3K/Akt/AP-1 cascade may be critical for colon cancer cells to metastasize. Based on our results, we suggest that the modification of IGF-1, PTEN, or PI3K function might be promising new therapeutic approaches to inhibit the aggressive spread of colon cancer.